Preparation method of negative electrode of lithium battery and lithium battery
By in situ synthesis and heat treatment on nickel foam, nitrogen-doped carbon-coated zinc nanoparticles were formed, the problem of poor combination of lithium-philic materials and current collectors was solved, orderly deposition and peeling of lithium metal was achieved, and lithium was improved Battery Coulomb efficiency and cycle life.
Patent Information
- Application Number
- CN202411540871.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, the combination of lithium-philic materials and current collectors is not strong, resulting in the lithium metal being easily shedding during the deposition and desorption process, affecting the Coulomb efficiency and service life of lithium batteries.
The zinc-based organometallic frame is synthesized in situ on nickel foam and formed nitrogen-doped carbon-coated zinc nanoparticles by heat treatment, which are loaded onto the current collector as a lithium-philic material to enhance the binding force with nickel foam.
The orderly deposition and peeling process of lithium metal is improved, and the Coulomb efficiency and cycle life of the negative electrode of lithium battery are enhanced.
Smart Images

Figure CN119419221A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy, and in particular to lithium batteries. Background Art
[0002] Lithium metal is considered to be one of the most promising negative electrode materials for lithium batteries due to its high specific capacity, low working potential and high energy density. Guiding the orderly deposition of lithium metal, inhibiting the growth of lithium dendrites and the volume expansion during lithium deposition and desorption can effectively improve the coulombic efficiency and cycle life of lithium metal negative electrodes. In recent years, lithium-philic materials loaded on three-dimensional porous current collectors have been widely used for lithium metal negative electrodes. On the one hand, the three-dimensional current collector has a high specific surface area, which can effectively reduce the local current density of the electrode and make the lithium metal deposition more uniform; on the other hand, the porous structure has enough space to store lithium, reducing the impact of lithium dendrite growth on the safety of lithium batteries. Lithium-philic materials can guide lithium metal to deposit uniformly throughout the current collector. However, the current research shows that the combination of lithium-philic materials and current collectors is not strong. During the deposition and desorption of lithium metal, they may fall off the current collector or even agglomerate. The uneven distribution of lithium-philic materials will promote the uneven deposition of lithium metal and reduce the coulombic efficiency and service life of the battery. Summary of the invention
[0003] The embodiments of the present application provide a method for preparing a negative electrode of a lithium battery and a lithium battery to solve the technical problem that the bonding between the lithium-philic material and the current collector is not strong.
[0004] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode of a lithium battery, the method for preparing a negative electrode of a lithium battery comprising the following steps:
[0005] Providing nickel foam with a porous structure;
[0006] Placing the nickel foam in a liquid environment containing zinc ions and 2-methylimidazole to synthesize a zinc-based organic metal framework on the surface of the nickel foam to obtain a current collector precursor having a zinc-based organic metal framework;
[0007] The current collector precursor having a zinc-based organic metal framework is placed in a mixed atmosphere of hydrogen and inert gas for heat treatment, so that the zinc-based organic metal framework of the current collector precursor forms nitrogen-doped carbon-coated zinc nanoparticles through a chemical reaction to obtain a current collector having the porous structure;
[0008] Lithium metal is prepared on the surface of the current collector to obtain the lithium battery negative electrode.
[0009] In some embodiments of the present application, the step of preparing lithium metal on the surface of the current collector comprises the following steps:
[0010] In an inert atmosphere, filling molten lithium metal into the porous structure of the current collector;
[0011] The molten lithium metal in the porous structure of the current collector is cooled and solidified to obtain the negative electrode of the lithium battery.
[0012] In some embodiments of the present application, filling molten lithium metal into the porous structure of the current collector in an inert atmosphere comprises the following steps:
[0013] In an inert atmosphere, the current collector is immersed in molten lithium metal for at least 5 minutes, so that the molten lithium metal is filled into the porous structure of the current collector.
[0014] In some embodiments of the present application, the preparation of lithium metal on the surface of the current collector is performed in a glove box.
[0015] In some embodiments of the present application, in the mixed atmosphere of hydrogen and inert gas, the volume ratio of hydrogen in the mixed atmosphere is 4% to 6%.
[0016] In some embodiments of the present application, the temperature of the heat treatment is 400-600° C.; and / or,
[0017] The heat treatment time is 1 to 3 hours.
[0018] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the negative electrode of the lithium battery is a lithium battery negative electrode prepared by the method described in any embodiment of the first aspect.
[0019] In some embodiments of the present application, the positive electrode of the lithium battery includes one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium cobalt oxide, lithium manganese oxide, and a lithium-rich solid solution.
[0020] In some embodiments of the present application, the lithium battery further includes a separator and a liquid electrolyte.
[0021] In some embodiments of the present application, the lithium battery also includes a solid electrolyte.
[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0023] The method for preparing the negative electrode of a lithium battery provided in an embodiment of the present application comprises in-situ synthesizing a metal organic framework on nickel foam, and then in-situ forming nitrogen-doped carbon-coated zinc nanoparticles on the nickel foam by heat treatment. The nitrogen-doped carbon-coated zinc nanoparticles are good lithium-philic materials and can guide the orderly deposition and stripping of lithium metal. The present application utilizes the relatively strong bonding property of the metal organic framework and nickel foam to enable the lithium-philic material nitrogen-doped carbon-coated zinc nanoparticles to be relatively firmly loaded onto the nickel foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0026] Figure 1 A schematic diagram of a process for preparing a negative electrode for a lithium battery provided in an embodiment of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0028] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0030] At present, there is a technical problem that the lithium-philic materials on the three-dimensional porous current collector are not strongly bonded with the current collector.
[0031] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0032] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode of a lithium battery, the method for preparing a negative electrode of a lithium battery comprising the following steps:
[0033] S1: providing a nickel foam having a porous structure;
[0034] S2: placing the nickel foam in a liquid environment containing zinc ions and 2-methylimidazole to synthesize a zinc-based organic metal framework on the surface of the nickel foam to obtain a current collector precursor having a zinc-based organic metal framework;
[0035] S3: placing the current collector precursor having a zinc-based organic metal framework in a mixed atmosphere of hydrogen and inert gas for heat treatment, so that the zinc-based organic metal framework of the current collector precursor forms nitrogen-doped carbon-coated zinc nanoparticles through a chemical reaction, thereby obtaining a current collector having the porous structure;
[0036] S4: preparing lithium metal on the surface of the current collector to obtain the negative electrode of the lithium battery.
[0037] It is easy to understand that the liquid environment containing zinc ions and 2-methylimidazole can be obtained by mixing 2-methylimidazole and a zinc salt solution.
[0038] It is easy to understand that zinc ions and 2-methylimidazole will react to form a zinc-based metal organic framework ZIF-8, and a portion of ZIF-8 will be generated in situ on the nickel foam. Since 2-methylimidazole can also coordinate with the empty orbital of nickel atoms, this makes the combination of ZIF-8 and nickel foam relatively firm.
[0039] It is easy to understand that heat treatment will cause ZIF-8 to decompose and carbonize, and zinc ions to be reduced by hydrogen, thereby forming nitrogen-doped carbon-coated zinc nanoparticles. Since the bond between ZIF-8 and nickel foam is relatively strong, the nitrogen-doped carbon-coated zinc nanoparticles formed by ZIF-8 are also relatively strong with nickel foam. Nitrogen-doped carbon-coated zinc nanoparticles have a high specific surface area and a large number of carbonyl groups, nitrogen-containing surface functional groups and zinc sites, which are conducive to inducing lithium metal to form crystal nuclei, thus having excellent affinity for lithium and being a good lithium-affinity material.
[0040] The beneficial effect of selecting nickel foam as the matrix material of the current collector in the present application is that the nickel foam and ZIF-8 have a strong bonding force, and the interior has a rich porous structure that can be used to accommodate lithium metal. The current collector still retains this porous structure, and the deposition of lithium metal can be carried out inside the current collector, and the impact of lithium dendrites on the diaphragm is relatively small; lithium metal is deposited in a porous structure with a smaller space, the growth of lithium dendrites is restricted, and the uneven growth of lithium dendrites is reduced, thereby increasing the orderliness of the lithium metal deposition and stripping process.
[0041] The present application can prepare lithium metal on the surface of the current collector by any feasible implementation method. As an example, the present application can prepare lithium metal on the surface of the current collector by electrochemical deposition, vapor deposition, impregnation of hot-melt lithium metal, etc. It should be noted that the current collector structure of the present application is based on nickel foam, which has a rich porous structure. The surface of the current collector described in the present application includes both a visible external surface and an internal surface formed by the porous structure.
[0042] In some embodiments, for electrochemical deposition, the present application can use the current collector as an initial lithium-free negative electrode and assemble it with a lithium-rich positive electrode material into a prefabricated lithium battery whose negative electrode does not contain lithium, and achieve the deposition of lithium metal on the current collector by charging the prefabricated lithium battery.
[0043] The present application synthesizes a metal organic framework in situ on nickel foam, and then forms nitrogen-doped carbon-coated zinc nanoparticles in situ on the nickel foam by heat treatment. The nitrogen-doped carbon-coated zinc nanoparticles are good lithium-philic materials and can guide the orderly deposition and stripping of lithium metal. The present application utilizes the relatively strong bonding property of the metal organic framework and nickel foam to load the lithium-philic material nitrogen-doped carbon-coated zinc nanoparticles onto the nickel foam relatively firmly.
[0044] In some embodiments of the present application, the step of preparing lithium metal on the surface of the current collector comprises the following steps:
[0045] S31: filling molten lithium metal into the porous structure of the current collector in an inert atmosphere;
[0046] S32: Cooling and solidifying the molten lithium metal in the porous structure of the current collector to obtain the negative electrode of the lithium battery.
[0047] It is easy to understand that lithium metal has poor mechanical processing performance, high chemical reactivity with moisture and oxygen under ambient conditions, and poor electrochemical reversibility, which makes ultra-thin lithium metal negative electrodes, whether prepared by mechanical processing or electrochemical deposition, have high requirements for the preparation process and preparation environment. The present application fills the porous structure of the current collector with molten lithium metal, and only needs to provide an inert atmosphere and heating conditions that can melt the lithium metal. The implementation is relatively simple, and the lithium metal can be relatively fully filled into the porous structure of the current collector.
[0048] In addition, it should be noted that the nitrogen-doped carbon-coated zinc nanoparticles are chemically inert and have good affinity to the strongly reducing molten lithium metal.
[0049] In some embodiments of the present application, filling molten lithium metal into the porous structure of the current collector in an inert atmosphere comprises the following steps:
[0050] S311: In an inert atmosphere, immersing the current collector in molten lithium metal for at least 5 minutes, so that the molten lithium metal fills the porous structure of the current collector.
[0051] In some embodiments of the present application, the preparation of lithium metal on the surface of the current collector is performed in a glove box.
[0052] It is easy to understand that the glove box is a commonly used equipment in the lithium battery field and can provide an inert atmosphere and heating conditions.
[0053] In some embodiments of the present application, in the mixed atmosphere of hydrogen and inert gas, the volume ratio of hydrogen in the mixed atmosphere is 4% to 6%.
[0054] It is easy to understand that nickel foam is a nickel metal product, and nickel metal has a strong ability to absorb hydrogen. The mechanical properties of nickel metal will deteriorate after absorbing hydrogen. The beneficial effect of the volume ratio of hydrogen in the mixed atmosphere being 4% to 6% is that it can fully reduce zinc ions without causing the nickel foam to absorb more hydrogen and deteriorate its mechanical properties.
[0055] As an example, the volume ratio of hydrogen in the mixed atmosphere may be 4%, 4.5%, 5%, 5.5%, or 6%.
[0056] In some embodiments of the present application, the temperature of the heat treatment is 400-600° C.; and / or,
[0057] The heat treatment time is 1 to 3 hours.
[0058] The heat treatment temperature of 400-600° C. has the beneficial effect of being conducive to the full reaction of the zinc-based organic metal framework and inhibiting the absorption of hydrogen by the nickel foam, while having low energy consumption and low load on equipment.
[0059] The beneficial effect of the heat treatment time of 1 to 3 hours is to reduce the time consumption of step S2 as much as possible on the basis of fully reacting the zinc-based organic metal framework, thereby improving the process efficiency.
[0060] In a second aspect, an embodiment of the present application provides a lithium battery, wherein the negative electrode of the lithium battery is a lithium battery negative electrode prepared by the method described in any embodiment of the first aspect.
[0061] The lithium battery is realized by a lithium battery negative electrode prepared by the method described in any embodiment of the first aspect. The specific implementation of the lithium battery can refer to the above embodiments and common knowledge in the art. Since the lithium battery adopts part or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0062] In some embodiments of the present application, the positive electrode of the lithium battery includes one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium cobalt oxide, lithium manganese oxide, and a lithium-rich solid solution.
[0063] In some embodiments of the present application, the positive electrode of the lithium battery further includes a conductive agent and a binder.
[0064] In some embodiments of the present application, the conductive agent includes at least one of carbon black, carbon nanotubes, and graphene; and / or,
[0065] The binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid.
[0066] In some embodiments of the present application, the lithium battery further includes a separator and a liquid electrolyte.
[0067] It is easy to understand that in the lithium battery negative electrode described in the present application, lithium dendrites mainly exist in the porous structure of the current collector, and fewer lithium dendrites are generated on the surface where the current collector contacts the diaphragm, which has less impact on the diaphragm. Therefore, the lithium battery negative electrode described in the present application can be applied to traditional lithium batteries including a diaphragm and a liquid electrolyte.
[0068] In some embodiments of the present application, the lithium battery also includes a solid electrolyte.
[0069] It is easy to understand that the lithium battery negative electrode described in the present application is suitable for lithium batteries that do not contain a separator and use a solid electrolyte.
[0070] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0071] Example 1
[0072] This embodiment provides a lithium battery negative electrode, which is prepared by the following method:
[0073] Dissolve 1.17 g Zn(NO3)2·6H2O in 8 g deionized water to obtain zinc nitrate solution;
[0074] Dissolve 22.70 g of 2-methylimidazole in another 80 g of deionized water to obtain a 2-methylimidazole solution;
[0075] The zinc nitrate solution and the 2-methylimidazole solution were stirred and mixed, and the nickel foam was added;
[0076] The two solutions were mixed and stirred for 30 minutes, the nickel foam was washed with deionized water, and then dried to obtain a current collector precursor;
[0077] The current collector precursor is placed in a tube furnace, reacted at 400° C. for 2 h in a hydrogen-argon mixed atmosphere with a hydrogen volume percentage of 5%, to obtain a current collector;
[0078] In a glove box filled with nitrogen, the current collector was immersed in molten metal Li and taken out after 5 minutes to obtain the negative electrode of the lithium battery.
[0079] This embodiment also provides a lithium battery, which is prepared by the following method:
[0080] Providing a positive electrode plate, the positive electrode plate is composed of a positive electrode active material, a conductive agent, and a binder in a mass ratio of 95:3:2, wherein the positive electrode active material is lithium cobalt oxide, the conductive agent is SUPERP carbon black, and the binder is sodium carboxymethyl cellulose;
[0081] Providing a polyethylene diaphragm and an electrolyte, wherein the electrolyte is an ethylene carbonate solution of lithium hexafluorophosphate;
[0082] The positive electrode plate and the polyethylene separator are stacked in a Z-shaped stacking manner, and a 1Ah lithium battery is prepared through welding, liquid injection, pre-charging, secondary sealing, and formation processes.
[0083] Example 2
[0084] This embodiment provides a lithium battery negative electrode, which is prepared by the following method:
[0085] Dissolve 1.17 g Zn(NO3)2·6H2O in 8 g deionized water to obtain zinc nitrate solution;
[0086] Dissolve 22.70 g of 2-methylimidazole in another 80 g of deionized water to obtain a 2-methylimidazole solution;
[0087] The zinc nitrate solution and the 2-methylimidazole solution were stirred and mixed, and the nickel foam was added;
[0088] The two solutions were mixed and stirred for 30 minutes, the nickel foam was washed with deionized water, and then dried to obtain a current collector precursor;
[0089] The current collector precursor is placed in a tube furnace, reacted at 500° C. for 2 h in a hydrogen-argon mixed atmosphere with a hydrogen volume percentage of 5%, to obtain a current collector;
[0090] In a glove box filled with nitrogen, the current collector was immersed in molten metal Li and taken out after 5 minutes to obtain the negative electrode of the lithium battery.
[0091] This embodiment also provides a lithium battery, which is prepared by the following method:
[0092] Providing a positive electrode plate, the positive electrode plate is composed of a positive electrode active material, a conductive agent, and a binder in a mass ratio of 95:3:2, wherein the positive electrode active material is lithium manganate, the conductive agent is KS-6 carbon black, and the binder is sodium carboxymethyl cellulose;
[0093] Providing a polyethylene diaphragm and an electrolyte, wherein the electrolyte is an ethylene carbonate solution of lithium hexafluorophosphate;
[0094] The positive electrode plate and the polyethylene separator are stacked in a Z-shaped stacking manner, and a 1Ah lithium battery is prepared through welding, liquid injection, pre-charging, secondary sealing, and formation processes.
[0095] Example 3
[0096] This embodiment provides a lithium battery negative electrode, which is prepared by the following method:
[0097] Dissolve 1.17 g Zn(NO3)2·6H2O in 8 g deionized water to obtain zinc nitrate solution;
[0098] Dissolve 22.70 g of 2-methylimidazole in another 80 g of deionized water to obtain a 2-methylimidazole solution;
[0099] The zinc nitrate solution and the 2-methylimidazole solution were stirred and mixed, and the nickel foam was added;
[0100] The two solutions were mixed and stirred for 30 minutes, the nickel foam was washed with deionized water, and then dried to obtain a current collector precursor;
[0101] The current collector precursor is placed in a tube furnace, reacted at 400° C. for 2 h in a hydrogen-argon mixed atmosphere with a hydrogen volume percentage of 5%, to obtain a current collector;
[0102] In a glove box filled with nitrogen, the current collector was immersed in molten metal Li and taken out after 5 minutes to obtain the negative electrode of the lithium battery.
[0103] This embodiment also provides a lithium battery, which is prepared by the following method:
[0104] Providing a positive electrode plate, the positive electrode plate is composed of a positive electrode active material, a conductive agent, and a binder in a mass ratio of 95:3:2, wherein the positive electrode active material is lithium cobalt oxide, the conductive agent is SUPER P carbon black, and the binder is polyacrylic acid;
[0105] Providing a polyethylene diaphragm and an electrolyte, wherein the electrolyte is an ethylene carbonate solution of lithium hexafluorophosphate;
[0106] The positive electrode plate and the polyethylene separator are stacked in a Z-shaped stacking manner, and a 1Ah lithium battery is prepared through welding, liquid injection, pre-charging, secondary sealing, and formation processes.
[0107] Comparative Example
[0108] The only difference between this comparative example and Example 1 is that in this comparative example, zinc nanoparticles are directly loaded on nickel foam instead of nitrogen-doped carbon-coated zinc nanoparticles.
[0109] The details are as follows:
[0110] Dissolve 1.17 g Zn(NO3)2·6H2O in 8 g deionized water to obtain zinc nitrate solution;
[0111] Add nickel foam to zinc nitrate solution;
[0112] Taking out and drying the nickel foam to obtain a current collector precursor;
[0113] The current collector precursor is placed in a tube furnace, reacted at 400° C. for 2 h in a hydrogen-argon mixed atmosphere with a hydrogen volume percentage of 5%, to obtain a current collector;
[0114] In a glove box filled with nitrogen, the current collector was immersed in molten metal Li and taken out after 5 minutes to obtain the negative electrode of the lithium battery.
[0115] This comparative example also provides a lithium battery, which is prepared by the following method:
[0116] Providing a positive electrode plate, the positive electrode plate is composed of a positive electrode active material, a conductive agent, and a binder in a mass ratio of 95:3:2, wherein the positive electrode active material is lithium cobalt oxide, the conductive agent is SUPER P carbon black, and the binder is sodium carboxymethyl cellulose;
[0117] Providing a polyethylene diaphragm and an electrolyte, wherein the electrolyte is an ethylene carbonate solution of lithium hexafluorophosphate;
[0118] The positive electrode plate and the polyethylene separator are stacked in a Z-shaped stacking manner, and a 1Ah lithium battery is prepared through welding, liquid injection, pre-charging, secondary sealing, and formation processes.
[0119] Related experiments and effect data:
[0120] At a current of 1C, the lithium batteries of Examples 1 to 3 and the comparative example were subjected to cyclic charge and discharge tests, and the statistically obtained capacity retention rate after 30 cycles and the number of cycles at which the capacity retention rate was 80% are shown in Table 1.
[0121] Table 1
[0122] Capacity retention after 30 cycles Cycle number for 80% capacity retention Example 1 92% 180 Example 2 95% 260 Example 3 88% 150 Comparative Example 85% 45
[0123] It can be found from Table 1 that for the lithium batteries provided in Examples 1 to 3, the capacity retention rate after 30 cycles and the number of cycles at which the capacity retention rate is 80% are both at a relatively high level. However, the capacity retention rate after 30 cycles and the number of cycles at which the capacity retention rate is 80% are significantly lower than those in Examples 1 to 3 for the lithium batteries provided in the comparative example. In the comparative example, zinc nanoparticles are loaded on the nickel foam, while in Examples 1 to 3, nitrogen-doped carbon-coated zinc nanoparticles formed by the reaction of a zinc-based organic metal framework are loaded on the nickel foam. Since the zinc-based organic metal framework has a strong binding ability with nickel metal, the nitrogen-doped carbon-coated zinc nanoparticles are also firmly bound to the nickel foam, thereby inducing orderly deposition or stripping of lithium metal, thereby making the cycle performance of Examples 1 to 3 more excellent than that of the comparative example.
[0124] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0125] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.
[0126] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a negative electrode of a lithium battery, characterized in that: The method comprises the following steps: Providing nickel foam with a porous structure; Placing the nickel foam in a liquid environment containing zinc ions and 2-methylimidazole to synthesize a zinc-based organic metal framework on the surface of the nickel foam to obtain a current collector precursor having a zinc-based organic metal framework; The current collector precursor having a zinc-based organic metal framework is placed in a mixed atmosphere of hydrogen and inert gas for heat treatment, so that the zinc-based organic metal framework of the current collector precursor forms nitrogen-doped carbon-coated zinc nanoparticles through a chemical reaction to obtain a current collector having the porous structure; Lithium metal is prepared on the surface of the current collector to obtain the lithium battery negative electrode.
2. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The step of preparing lithium metal on the surface of the current collector comprises the following steps: In an inert atmosphere, filling molten lithium metal into the porous structure of the current collector; The molten lithium metal in the porous structure of the current collector is cooled and solidified to obtain the negative electrode of the lithium battery.
3. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The step of filling molten lithium metal into the porous structure of the current collector in an inert atmosphere comprises the following steps: In an inert atmosphere, the current collector is immersed in molten lithium metal for at least 5 minutes, so that the molten lithium metal is filled into the porous structure of the current collector.
4. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The preparation of lithium metal on the surface of the current collector is performed in a glove box.
5. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: In the mixed atmosphere of hydrogen and inert gas, the volume ratio of hydrogen in the mixed atmosphere is 4% to 6%.
6. The method for preparing a negative electrode of a lithium battery according to claim 1, characterized in that: The heat treatment temperature is 400-600° C.; and / or, The heat treatment time is 1 to 3 hours.
7. A lithium battery, characterized in that: The negative electrode of the lithium battery is a negative electrode of the lithium battery prepared by the method according to any one of claims 1 to 6.
8. The lithium battery according to claim 7, characterized in that: The positive electrode of the lithium battery includes one of a nickel-cobalt-manganese ternary material, a nickel-cobalt-aluminum ternary material, lithium cobalt oxide, lithium manganese oxide, and a lithium-rich solid solution.
9. The lithium battery according to claim 7, characterized in that: The lithium battery also includes a separator and a liquid electrolyte.
10. The lithium battery according to claim 7, characterized in that: The lithium battery also includes a solid electrolyte.
Citation Information
Patent Citations
Three-dimensional current collector modified with non-noble metal coating
CN109950547A
Composite metal lithium negative electrode, preparation method and metal lithium battery
CN110649267A
Method for preparing three-dimensional metal lithium negative electrode by using MOFs derivative
CN114122332A
Negative current collector, preparation method thereof, negative pole piece with negative current collector, and lithium secondary battery
CN115842133A
Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and power utilization device
CN118056291A